Modernism and cultural conflict, 1880-1922 - Ardis, Ann L., 1957- (Cambridge University Press, 2002)
Ardis questions commonly held views of the radical nature of literary modernism. She positions the coterie of writers centered around Pound, Eliot, and Joyce as one among a number of groups in Britain intent on redefining the cultural work of literature at the turn of the twentieth century.